Development and Validation of a Sustainable Behavior Scale for Generation Z in Indonesia - Annisa Melany Sukri; Mohammad Nursalim Malay; Nurul Isnaeni Isnaeni (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Abstract : Environmental sustainability challenges are intensifying alongside climate change, while Generation Z constitutes Indonesia’s largest and most strategic demographic group, making their sustainable behavior vital for national development. This study aimed to develop and validate a contextually relevant Sustainable Behavior Scale for Indonesian Generation Z. Using a quantitative psychometric approach, data were collected from 486 respondents aged 16–28 years. Scale development was grounded in Corral Verdugo’s multidimensional framework and examined using Exploratory Factor Analysis with minimum residual extraction and oblimin rotation. The analysis demonstrated adequate sampling adequacy (KMO = 0.781) and a significant Bartlett’s Test of Sphericity (p .001). A five-factor structure consisting of 19 items emerged, explaining 45.8% of the total variance. These factors represent behavioral dimensions of sustainable behavior in everyday life rather than causal determinants, including pro-ecological daily practices, resource conservation behavior, social responsibility and collective sustainability, fairness and intergenerational concern, and responsible consumption and lifestyle choices. The measurement model showed good fit (RMSEA = 0.049; TLI = 0.909) and acceptable internal consistency (α = 0.717). This study offers one of the first empirically validated multidimensional sustainable behavior scales tailored to Indonesian Generation Z, providing a robust instrument for future research.